An Existence Theorem for Some Nonlinear Volterra-Fredholm Integral Equations in the Space of Continuous Tempered Functions. (18th August 2021) - Özdemir, İsmet
Abstract: The aim of the present paper is to study the existence and asymptotic behavior of the solutions of some functional integral equations which contain a number of classical nonlinear integral equations as special cases. The main tools used in our considerations are the concept of a measure of noncompactness and the classical Schauder fixed point principle. The investigations of the paper are placed in the space of continuous and tempered functions on the real half-line. The applicability of the results is illustrated by examples.